Strong Sexual Selection Does Not Induce Population Differentiation in a Fish Species with High Dispersal Potential: The Curious Case of the Worm Pipefish Nerophis lumbriciformis (Teleostei: Syngnathidae). (12th December 2020) - Mendes, Tito; Gomes, Cidália; Monteiro, Nuno; Antunes, Agostinho
Abstract: High levels of population differentiation are a common demographic pattern in syngnathids, even at small geographical scales. This is probably the end result of the common life history traits observed within the family, involving limited dispersal capabilities and strong habitat dependency. The worm pipefish, Nerophis lumbriciformis, which displays all these characteristics, also presents an additional variable potentially able to promote population differentiation: high sexual selection intensity, especially at the extremes of its distribution. Nevertheless, an early life pelagic stage, which presumably allows for admixture, could prevent population structuring. Here, we assessed the phylogeography of N. lumbriciformis through the amplification of the cytochrome b, 12S, and 16S rDNA mitochondrial markers as well as the rhodopsin nuclear marker, performed upon 119 individuals. We observed a genetically homogeneous population with indications of extensive gene flow. We tentatively attribute this finding to the dispersal potential of the species' pelagic larvae, supported by marine currents acting as major dispersal vectors. We also detected a signal of expansion towards the poles, consistent with the current climate change scenario. Despite the marked latitudinal differences in the phenotype of reproducing worm pipefish, the absence of clear population structuring suggests that phenotypic plasticity can have a significant role in the expression of sexual selection-related traits.